On determination of some exact solutions of the stationary Navier-Stokes equations - Iurie Baltag (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
In this paper, various exact solutions of the stationary Navier-Stokes equations, which describe the planar flow of an incompressible liquid (or gas), are determined, i.e., solutions containing the components of the velocity of flow - the functions